Can a more performance-based setting bring additional efficiency to EU cohesion policy? - Francesco Molica; Anabela Marques Santos; Andrea Conte (European Commission, Joint Research Centre (JRC), 2023)
The paper investigates cohesion policy programmes' ability to define accurate policy outputs, in the form of targets. More specifically, the analysis explores the extent to which targets set by ERDF programmes to assess their performance are revised over time and seeks to identify specific patterns in relation to different areas (spending categories; typology of regions; etc.). The results point to significant challenges experienced by programmes in producing realistic targets as a vast majority of these are subject to frequent and significant amendments over the course of the programming period. The paper brings valuable evidence to the emerging debate as to whether embracing a full performance-based approach making the funds conditional upon the achievement of outputs/results would improve the efficiency and effectiveness of cohesion policy.
Keywords: H11; H83; R58; 330; cohesion policy; Recovery and Resilience Facility; ERDF; performance; European Union